Brazil Nut (Bertholettia excelsa H.B.K.) Selenium Distribution and Physical Chemical Characteristics of Shell, Brown Skin and Edible Part from Two Amazon Regions - Manfio, Daniel; Rodrigues, Manuel N. F; Savi, Geovana D; Scussel , Vildes M. (Asian Journal of Agriculture and Rural Development, 2012)
Brazil nuts (Bertholettia excelsa H.B.K.) shell, brown skin and edible part from Eastern (E) and Central-Western (C-W) Amazon regions were evaluated for their selenium (Se) distribution, physical chemical characteristics regarding proximate composition, nut ratio and water availability (moisture content and water activity). Nuts samples were collected from two factories located in Manaus and Cameta cities (C-W and E, respectively) to where they are delivered from each State (Amazonas and Para) for processing. Se analysis was carried out by mass spectrometry with inductively coupled plasma, proximate composition by the AOAC official methods and nut ration by gravimetry. Se levels varied among nut parts from the shell to edible part as follows: shell<brown skin<edible part with 0.44/0.31<20.58/6.12<44.13/19.25 mg/kg for Manaus/Cameta. Regarding lipid and protein content, they were low for shell and brown skin, however high in dietary fiber (57.17%). The shell/brown skin/edible part ratio was 4.2/3.8 g (1.2). Brown skin weight was only 1.23.05 g of the whole nut. Se is a powerful antioxidant for human metabolism balance being the highest concentration detected in the edible part. From the discarded nuts parts, the brown skin had the highest percentage of that element, especially those from C-W region which could be used as a source of Se in different food applications. As expected the shell and brown skin showed low level of lipids and proteins, however quite high fiber content, especially the brown skin which is quite promising on the food fiber enrichment point of view.